Penyuluhan Kesehatan Tentang Anemia dan Pentingnya Konsumsi Tablet Tambah Darah di SMP Muhammadiyah 61 Tanjung Selamat - Fadilah, Sylva Qamara Nur; Siregar, Zahwatul Hasanah; Nathasya, Diva Aulia; Vanesa, Khairiyah Dwi; Ritonga, Aina Fitrah Aulia; Saragih, Eka Fitria; Mahendra, Akmal Fiqhi Ranu (Universitas Muhammadiyah Sukabumi, 2023)
Anemia in adolescents is one of the significant health problems, affecting their growth, development, and well-being, attention to the problem of anemia in adolescents is very important in the context of prevention and early treatment efforts. This study aims to conduct health counseling at SMP Muhammadiyah 61 Tanjung Selamat about anemia and educate students about the importance of consuming blood-added tablets. The counseling method involves presentations, questions and answers, and educational games. Counseling participants consisted of students of SMP Muhammadiyah 61 class VII and IX in the age range of 12-15 years. The results of this activity show an increase in students' knowledge about anemia and its impact on health. In addition, their understanding of the benefits of blood-added tablets has also increased. Post-counseling evaluations showed that the majority of students expressed readiness to adopt positive changes in diet and take blood-added tablets.